THE INFLUENCE OF PRICE PERCEPTION, BRAND IMAGE, AND PRODUCT QUALITY ON BUYING INTEREST IN IPHONE SMARTPHONE PRODUCTS (A STUDY ON CONSUMERS IN SIDOARJO) - Angraini Putri Imawati; Mochamad Rizal Yulianto; Rita Ambarwati Sukmono (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: The rapid advancement of technology has significantly impacted consumer purchasing decisions, particularly in selecting smartphones. Consumers often consider factors like brand image, price perception, and product quality when choosing products. Specific Background: Among the vast range of smartphone options available, iPhone is a prominent choice, but the specific factors driving consumer interest in iPhone products, particularly in Sidoarjo, remain underexplored. Knowledge Gap: While much research has focused on general smartphone buying behavior, limited attention has been given to the specific interplay between price perception, brand image, and product quality in influencing buying interest for iPhones in regional markets like Sidoarjo. Aims: This study aims to examine the impact of price perception, brand image, and product quality on consumer buying interest in iPhone products in Sidoarjo, using Structural Equation Modeling (SEM) and Partial Least Squares (PLS) analysis. Results: From a sample of 110 respondents, the findings reveal that price perception, brand image, and product quality all have a significant positive effect on consumer buying interest. The R-square value of 0.700 suggests that 70% of the variation in buying interest is explained by these three variables. Novelty: This study provides novel insights into the Sidoarjo market, demonstrating that these factors substantially drive iPhone purchase interest, with brand reputation and perceived product quality playing key roles. Implications: The results highlight the importance of enhancing brand image and maintaining high product quality to increase consumer interest, which could inform marketing strategies for smartphone brands targeting regional markets like Sidoarjo. Future studies could explore additional variables influencing buying interest, given that 30% of the variation remains unexplained by the current model.